COMPARATIVE STUDY FOR DEVELOPING CLOSED VERNACULAR SETTLEMENTS IN EGYPT - H Eldardiry, Dr. Dalia; H Eldardiry, Dr. Islam (IJRDO - Journal of Social Science and Humanities Research, 2016)
From the observation of the urban settlements in Egypt from the past to the present, within research, it was monitored the closed vernacular communities developing in Egypt. Therefore, the core of the research was directing towards comparing between the two vernacular settlements; one from the past, the establishing of Cairo city, the other from the present, Al-Rehab City. Architectural principals are the main features of the comparison, then the followed by urban components that include; residential buildings, public buildings, and urban fabric as well. Consequently, the paper covered the social and culture factors that encouraged people to residence within the past and the present in the two eras, which will reflect positively upon solving people urban problems and avoid creating slum areas. This paper includes two stages to compare between the two vernacular settlements in the different era; a theoretical background in the literature provides architectural and urban features and social criteria for establishing of Cairo city, in 640 AD. Then, it comes to the analysis of the collected data in the current era for Al-Rehab City. The paper incorporates two methods of data collection. First, a field surveys among Al-Rehab City and obtained maps to determine the principal architectural and urban components. Second, a questionnaire survey of the residences was done to explain the factors that encouraged them to live in this closed vernacular settlement in the current era. Consequently, the paper compares between the two settlements to guide the planners to develop interactive vernacular settlements in Egypt.